1959
DOI: 10.2136/sssaj1959.03615995002300030022x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Fertilization and Clipping on Grass Roots

Abstract: Strategic placement of P32 and root excavations revealed that roots of orchardgrass and bromegrass reached a greater depth when no N was applied. Nitrogen increased the root diameter and decreased the rate of elongation causing the plants to feed near the soil surface for a longer period of time. Defoliation stopped root growth within 24 hours and induced decomposition of the existing roots within 36 to 48 hours. Uptake of P32 placed in the existing root zone 24 to 48 hours after clipping was not detected unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

1964
1964
1998
1998

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 0 publications
1
31
1
1
Order By: Relevance
“…Reports ofN effects on root distribution are contradictory. While Oswalt et al (1959) report that supplemental N decreased the rooting depth oforchardgrass and bromegrass and caused root proliferation and activity near the soil surface, Holt and Fisher (1960) reported that N fertilization of bermudagrass at rates up to 1400 kg N ha-t had no effect upon the amount of roots at any one depth nor was there any interaction of depth of rooting with N level although there was a trend towards deeper root penetration.…”
Section: Contamination Of the Root Samples Withmentioning
confidence: 98%
“…Reports ofN effects on root distribution are contradictory. While Oswalt et al (1959) report that supplemental N decreased the rooting depth oforchardgrass and bromegrass and caused root proliferation and activity near the soil surface, Holt and Fisher (1960) reported that N fertilization of bermudagrass at rates up to 1400 kg N ha-t had no effect upon the amount of roots at any one depth nor was there any interaction of depth of rooting with N level although there was a trend towards deeper root penetration.…”
Section: Contamination Of the Root Samples Withmentioning
confidence: 98%
“…There is pronounced diversion of carbohydrates from roots following defoliation (Kinsinger and Shaulis 1961;Gifford and Marshall 1973;Ryle and Powell 1975), and defoliation frequently reduces root growth (Crider 1955;Oswalt et al 1959). Sosebee and Wiebe (1971) found that defoliation and soil moisture interact to determine patterns of assimilate translocation.…”
mentioning
confidence: 99%
“…This would reduce the volume of soil the plant could utilise. Oswalt, Bertrand, and Teel (1959), using 32P, found that defoliation of cocksfoot and Bromus plants caused cessation of uptake of phosphate from 6 in. and lOin.…”
Section: Resultsmentioning
confidence: 99%